Valuation of the Durability of the Concrete Used in the Precast Great Soviet Panel System (2020)
The durability of the concrete of the precast Great Soviet Panel system is valued through the resistance to compression, ultrasonic pulse velocity, surface methods, humidity and potential of corrosion. The evaluation is approached, essentially, through experimental and statistical methods, nevertheless, historical-logical and technical methods, such as surveys and interviews, are used in order to gather a bigger amount of information on the resistance to compression of the elements in the original project. While analyzing the results, we can conclude that, in elements in a good technical-constructive state that conform the constructions in exploitation, concrete has an average resistance. However, in elements with the presence of pathological damages, the resistance is low due to the fact that elements show chemical deterioration processes caused by water exposure, which generates the formation of soluble paste compounds, loss of mass, and decrease in mechanical resistance, among other alterations. At the same time, carbonation of concrete is triggered, which, in turn, causes the corrosion of the reinforcing steel. This corrosion leads to the cracking of concrete, delamination of steel, decrease of the concrete-steel adhesion, and other manifestations that affect the durability of concrete. Therefore, the incidence of the durability of concrete should be valued in the structural seismic behavior of constructions.